Observing children with attachment difficulties in school : a tool for identifying and supporting emotional and social difficulties in children aged 5-11 - Golding, Kim S. (Jessica Kingsley Publishers, 2013)
An observational tool designed to help structure observations of children aged 5 â?? 11 with attachment issues in school. Simple checklists and diagrams help to identify emotional and behavioural problems, and hand-outs with activities are provided to provide emotional support and identify appropriate interventions.